The importance of swiss grants for creation of the carpathian euroregion marketing - Greta, М.; Otto, J. (Видавництво Львівської політехніки, 2013)
The content of the paper is the functioning of the Euro-regional structure in the integration structure of the European Union. Euroregions can influence the course of the integration process by influence on cross-border and inter-regional cooperation, and in the country of origin on cooperation with various socio-economic entities. To fulfill their role they need to "break through" and promotion. And this paper discussed the use of aid funds for promotion. Аналізується функціонування Єврорегіональної структури у структурі інтеграції Європейського Союзу. Єврорегіони можуть впливати на хід інтеграційних процесів, впливаючи на транскордонне та міжрегіональне співробітництво, а також у країні походження на співпрацю з різними соціально-економічними суб'єктами. Для виконання цієї ролі вони повинні "прорватися" і просунути себе. Описано використання коштів з фондів допомоги для просування.
Важливість шведських грантів для створення маркетингу карпатського єврорегіону
Keywords: Euroregion; Structural Funds; euroregional marketing; Єврорегіон; структурні фонди; єврорегіональний маркетинг